Investigation of morphometric variability of subthalamic nucleus, red nucleus, and substantia nigra in advanced Parkinson's disease patients using automatic segmentation and PCA‐based analysis. Issue 9 (19th February 2014) - Xiao, Yiming; Jannin, Pierre; D'Albis, Tiziano; Guizard, Nicolas; Haegelen, Claire; Lalys, Florent; Vérin, Marc; Collins, D. Louis
Abstract Subthalamic nucleus (STN) deep brain stimulation (DBS) is an effective surgical therapy to treat Parkinson's disease (PD). Conventional methods employ standard atlas coordinates to target the STN, which, along with the adjacent red nucleus (RN) and substantia nigra (SN), are not well visualized on conventional T1w MRIs. However, the positions and sizes of the nuclei may be more variable than the standard atlas, thus making the pre‐surgical plans inaccurate. We investigated the morphometric variability of the STN, RN and SN by using label‐fusion segmentation results from 3T high resolution T2w MRIs of 33 advanced PD patients. In addition to comparing the size and position measurements of the cohort to the Talairach atlas, principal component analysis (PCA) was performed to acquire more intuitive and detailed perspectives of the measured variability. Lastly, the potential correlation between the variability shown by PCA results and the clinical scores was explored. Hum Brain Mapp 35:4330–4344, 2014. © 2014 Wiley Periodicals, Inc.